Implementation of Fuzzy Logic in Temperature and Fermentation Time Control Systemon Alcohol Content of Cassava Tape Product - Siti Aqilah Hisanak Fauziyah; Alyaa Andriani Haniifah; Bunga Novia Ramadhan; Ernesto Bagus Suwito; Nasya Putri Aurelia; Puti Nayla Batrisyia Tobing; Tazkia Mutmainnah (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
The fermentation process of cassava tape involves complex biochemical reactions and requires careful attention to various factors. Temperature and fermentation time are crucial parameters that significantly affect the final quality of cassava tape. Along with the development of artificial intelligence (AI), the fermentation process can be controlled and monitored more precisely, thereby increasing the efficiency and consistency of the final product. This study aims to determine the Mamdani fuzzy logic approach in the temperature control system and fermentation duration in the cassava tape production process to optimally regulate the alcohol content of cassava tape. The research method is a literature study, testing Mamdani fuzzy logic using Matlab software, and analyzing input variables manually. The results of the study showed that the optimal temperature for cassava tape fermentation was between 25°C - 30°C and the optimal time for cassava tape fermentation was with a "long" duration. From the defuzzification results, the final results showed an alcohol content of 15.9% at a temperature of 29°C and a fermentation time of 80 hours so that the alcohol content of cassava tape was in accordance with the specifications.